Examining the Mediation Role of Parental Guilt in the Relationship between Working Mothers’ Smartphone Addiction and Their Children’s Problematic Technology Use - Sarıyıldız, Fatma Miray; Erus, Seher Merve (Addicta: The Turkish Journal on Addictions, 2025)
This study aimed to examine the mediation of parental guilt in the relationship between smartphone addiction in working mothers and problematic technology use among their preschool children. A total of 260 working mothers, aged between 22 and 50, with preschool children, participated in the study. The study utilized the “Personal Information Form,” “Smartphone Addiction Scale Short Form,” “Parental Guilt Scale,” and “Problematic Technology Use Scale for Children.” SPSS bootstrapping analysis was applied to investigate the mediation of parental guilt in the relationship between mothers’ smartphone addiction and their preschool children’s problematic technology use. The analysis revealed that parental guilt mediated the relationship between mothers’ smartphone addiction and their children’s problematic technology use. The findings are discussed considering existing knowledge on smartphone addiction, parental guilt, and problematic technology use in children. In this direction, suggestions are presented with a focus on working mothers to reduce problematic technology use among children.